Freight forwarding business of UTi Pership Pvt. Ltd.: focused on only air export - Hasan, Mohammed Mehedi (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.